2006
DOI: 10.1063/1.2361226
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Graphs with PCA-features for Improved Face Recognition

Abstract: Built on the principles of "Learning from Nature" and "Self-organization" Elastic Bunch Graph Matching for face recognition is a defining example for Organic Computing methodology. Here, we follow these principles further to advance the method in two respects. First, the requirement for manual annotation of landmarks is reduced to one single face, from which a self-organizing selection process gradually builds up the bunches by adding the most similar face to the bunch graph and then recalculating the matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, finding landmarks in the face was not the primary goal of this study. There are several ways to improve automatic processing of data including optimizing our current methods 11 or using additional heuristic methods to find the localization of the face in a given picture (Kalina, in preparation). Compared with the previous study, accuracy dropped slightly from 80 to 75%.…”
mentioning
confidence: 99%
“…However, finding landmarks in the face was not the primary goal of this study. There are several ways to improve automatic processing of data including optimizing our current methods 11 or using additional heuristic methods to find the localization of the face in a given picture (Kalina, in preparation). Compared with the previous study, accuracy dropped slightly from 80 to 75%.…”
mentioning
confidence: 99%
“…They must be initialized by manual annotation of facial images. In [5] we have presented a method that can automatically build good bunch graphs from only a few manually annotated images. This is also used for invariance learning in the second part of this paper.…”
Section: Elastic Bunch Graph Matchingmentioning
confidence: 99%
“…A comparison of the position of the eye nodes of the found graphs with ground truth data showed that all faces were located with adequate accuracy. A simpler version of this is described in [12]. n ≤ N N ).…”
Section: Landmark Findingmentioning
confidence: 99%